1992
DOI: 10.1007/bf01703061
|View full text |Cite
|
Sign up to set email alerts
|

Development of a supersensitive polymerase chain reaction method for human T lymphotropic virus type II (HTLV-II) and detection of HTLV-II proviral DNA from blood donors in Japan

Abstract: A supersensitive polymerase chain reaction procedure was developed to detect human T-lymphotropic virus type II (HTLV-II) proviral genome. Six primer pairs covering the various regions of HTLV-II were compared and selected on the basis of specificity and sensitivity. Among them, one primer pair of the pol region of HTLV-II (II pol) was able to amplify and detect even 0.1 fg of the cloned plasmid HTLV-II DNA (seven copies) by regular ethidium bromide staining on polyacrylamide gel. By using this procedure, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Levels of potassium in the control arm (y-irradiated only) were comparable with those previously found by Rivet et al [2] who noted levels of 30 mMat 4 days and Ramirez et al [3] who reported 68 mM K+ at 14 days. Walther-Wenker et al [4] made similar findings and now transfuse babies with BPF-4-filtered SAG-M product, irradiated and transfused at any time up to 14 days.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Levels of potassium in the control arm (y-irradiated only) were comparable with those previously found by Rivet et al [2] who noted levels of 30 mMat 4 days and Ramirez et al [3] who reported 68 mM K+ at 14 days. Walther-Wenker et al [4] made similar findings and now transfuse babies with BPF-4-filtered SAG-M product, irradiated and transfused at any time up to 14 days.…”
supporting
confidence: 79%
“…First, not all transfusions of bacterially contaminated blood components cause fever [2], Second, when fevers occur in septic transfusion reactions, temperature eleva tions may overlap the range of fevers from nonseptic reactions [2,3]. Third, febrile platelet transfusion reactions are caused frequently by inflammatory cytokines released from leukocytes during storage [5], or by alloimmune reactions to leukocyte antigens [6], reducing the specificity of fever as an indicator of a septic platelet transfusion reac tion.…”
Section: K E Olsen S G Sandlermentioning
confidence: 99%
See 3 more Smart Citations